The Effectiveness of the Audit Committee in Reducing Tax Avoidance in Mining Companies in Indonesia with External Audit Quality as a Moderating Variable - Muhammad Aganthasyah; Kusharyanti Kusharyanti; Januar Eko Prasetio (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of the audit committee on tax avoidance practices and to examine the role of external audit quality as a moderating variable. The results show that the audit committee significantly reduces the level of tax avoidance. Companies with independent and competent audit committees tend to demonstrate better tax compliance. Furthermore, external audit quality is proven to strengthen the influence of the audit committee in suppressing tax avoidance practices. High-quality external auditors, particularly those from Big Four firms, are more effective in enhancing oversight and detecting potential financial report manipulation related to tax obligations. These findings highlight the importance of corporate governance and external supervision in promoting tax compliance.